2017
DOI: 10.1007/s12603-016-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of the Dietary Inflammatory Index among African Americans

Abstract: Objectives Chronic inflammation is linked to many chronic conditions. One of the strongest modulators of chronic inflammation is diet. The Dietary Inflammatory Index (DII) measures dietary inflammatory potential and has been validated previously, but not among African Americans (AAs). Design Cross-sectional analysis using baseline data from the Healthy Eating and Active Living in the Spirit (HEALS) intervention study. Setting Baseline data collection occurred between 2009 and 2012 in or near Columbia, SC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 25 publications
5
74
0
2
Order By: Relevance
“…Another limitation is that only 27 of the 45 food parameters identified in the original literature search were available to calculate the E-DII in our study. We were also unable to validate the E-DII scores with inflammatory biomarkers in the AACES population; however, a recent study 18 validated the E-DII in an African American population by correlating the E-DII scores and CRP concentrations. The literature search for the DII has not been updated since 2010; however, with each literature update, the DII scores have remained relatively stable over time.…”
Section: Cancer Epidemiologymentioning
confidence: 90%
See 2 more Smart Citations
“…Another limitation is that only 27 of the 45 food parameters identified in the original literature search were available to calculate the E-DII in our study. We were also unable to validate the E-DII scores with inflammatory biomarkers in the AACES population; however, a recent study 18 validated the E-DII in an African American population by correlating the E-DII scores and CRP concentrations. The literature search for the DII has not been updated since 2010; however, with each literature update, the DII scores have remained relatively stable over time.…”
Section: Cancer Epidemiologymentioning
confidence: 90%
“…to reflect the literature on diet and inflammation through 2010. The improved DII has been validated by examining its relationship to inflammatory biomarkers ( e.g ., CRP and interleukin‐6) . Additionally, a more pro‐inflammatory diet, as defined by higher DII scores, has been linked to an increased risk of several cancers, including colorectal, pancreatic, prostate, breast and endometrial cancer .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Dietary Inflammatory Index (DII) has been developed, a dietary tool which determines the inflammatory potential of an specific individual diet [9]. The DII has been originally validated with several inflammatory biomarkers by Shivappa et al [9], and later validated in different populations with inflammatory biomarkers [10][11][12]. Therefore, a high DII (i.e., a pro-inflammatory diet) may be associated with increased risk of suffering chronic diseases and/or all-cause mortality in humans [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…The first construct validation, against hs-CRP, was conducted in the SEASONS study [32]. Subsequently, construct validations have examined the association between DII score and serum levels of hs-CRP, IL-6, and TNF-α in several populations [33][34][35][36]. In addition, multiple studies demonstrated the positive link between adherence to proinflammatory diet (the higher DII score) and levels of serum glucose, as well as, the association between the DII score and serum levels of lipid profile [37][38][39][40].…”
mentioning
confidence: 99%